The Effects of Tofacitinib-Mediated Janus Kinase/Signal Transducers and Activators of the Transcription Signal Pathway Inhibition on Collagen Biosynthesis in Hepatic and Skin Fibroblast Cell Culture - Mehtap ŞAHİN,; Hüseyin AYDIN,; Ahmet ALTUN,; Mehmet Emin DERİN,; Ali ŞAHİN, (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the effects of Janus kinase/signal transducers and activators of the transcription (JAK/STAT) pathway inhibition on collagen biosynthesis in fibroblast cell culture by tofacitinib. Materials and methods: BJ-CRL-1474® (skin) and BRL3A® (hepatic) fibroblast cell cultures were proliferated in a suitable medium. Tofacitinib was administered to fibroblast cells proliferating in 96-well flasks at concentrations of 25, 50, 100, 200, 400, and 800 nM. Tissue inhibitor of metalloproteinase-1 (TIMP-1), matrix metalloproteinase-3 (MMP-3), transforming growth factor beta 1 (TGF-β1), and hydroxyproline levels were measured using the enzyme-linked immunosorbent assay method. Results: Tofacitinib showed cytotoxic effect on skin and liver cell culture. The cytotoxic effect of tofacitinib started at 100 nM (p<0.05). The highest effect was obtained at 800 nM. The time-dependent cytotoxic effect of tofacitinib was significantly higher at all concentrations after 72 hours than at 24 and 48 hours (p<0.05). The level of TGF-β1 was significantly lower even at a tofacitinib concentration of 25 nM (p<0.05). There were significant decreases in MMP-3, TIMP-1, and hydroxyproline levels after tofacitinib administration (p<0.05). Conclusion: Tofacitinib inhibited fibroblast cell proliferation in a concentration-dependent manner in a fibroblast cell culture. However, further extensive animal and human studies are necessary to determine the clinical significance of this effect.